Медиа и власть: современные концептуализации - Кучма, И. (Социология: теория, методы, маркетинг, 2004)
This article examines contemporary approaches to mediapower relations. Power is
represented not only by political institutions, governmental bodies and public administration, but also by rules, norms and cultural stereotypes that form behavioral
strategies of social groups. Sustainable political and economical systems in the society
are legitimized by cultural system. It is based on cultural capital shaped par excellance
by symbolic power and popular culture and formed and broadcasted by the media
culture (mass media). Media culture has a dual essence: on the one hand, media
institutions are mainly politically and economically dependent on dominant political
institutions, on the other hand, political institutions depend on the mass media as the
major communication channel and space for pubic dialogs in society. All these contradictions are reflected in the news discourses examined in terms of different approaches, including ideological tools.